Compact radio sources: Triggering and feedback. Issue 9 (26th October 2021) - Tadhunter, Clive; Morganti, Raffaella; Santoro, Francesco; Bernhard, Emmanuel
Abstract: CSS/GPS objects represent a key stage in the evolution of powerful radio AGN in which the jets are expanding through the denser, kpc‐scale ISM in the host galaxies. Therefore, it is important both to understand how such radio AGN are triggered as galaxies evolve and to directly quantify the impact of the outflows induced by the jet‐cloud interactions. Here, we show that CSS/GPS sources are likely to be triggered in galaxy mergers, just like powerful radio AGN in general. However, they are both more gas‐rich and have higher star formation rates on average than their more extended counterparts. Also, whereas observations frequently show evidence for strong jet‐cloud interactions in CSS/GPS in the form of warm outflows, in most cases these warm outflows are unlikely to be energetic enough to affect the star formation histories of the entire host galaxies outside the central kpc. Rather, much of the mass, energy, and momentum of the outflows appear to be tied up in neutral and molecular outflows, which may have a more important impact on the host galaxies. Finally, we consider whether CSS/GPS sources are impostors in flux‐limited samples due to the effect of the strong jet‐cloud interactions on their radio luminosities.